FORMULASI MEDIA PERTUMBUHAN MISELIUM JAMUR TIRAM PUTIH (Pleurotus ostreatus (Jacq) P. Kumm) DENGAN SUPLEMENTASI LIMBAH SABUT KELAPA - Sitti Masyitah; Umrah Umrah (Biocelebes, 2020)
The research entitled Formulation of media for growth of white oyster mushroom mycelium ((Pleurotus ostreatus (Jacq) P. Kumm) with waste of coconut fiber supplementation was carried out out in Biotechnology Laboratory unit, Department of Biology, Faculty of Mathematics and Natural Sciences. This research purposes; (a) To find out the formulation of coconut fiber waste as a supplementary medium for growing white oyster mushrooms (P.ostreatus); (b) to find out the formulation at the maximum dose of coconut husk supplementation in the medium for good growth of white oyster mushrooms (P.ostreatus). This study was designed based on a Completely Randomized Design (CRD) consisting of 7 settings and 4 replications. The help arrangement is given between Sawdust: Rice Bran: Lime: Coconut Fiber Waste. Namely M0 (Basic media 100%, without Supplements), M1 Basic media 95% + Supplements 5%, M2 (Basic media 90% + Supplements 10%), M3 (Basic media 85% + Supplements 15%), M4 (Basic media 80% + Supplement 20%), M5 (Basic media 75% + Supplement 25%), M6 (Basic media 70% + Supplement 30%). Observation parameters; (a) prohibiting mycelium; (B) Incubation time; (c) Number of colonies (Colony Forming Units); (d) Macroscopic and microscopic observations of mycelium. The results showed that the fastest mycelium growth in M6 treatment was 1.193 cm and the lowest was M0 treatment which was 1.123 cm. The lowest incubation time at M6 is 28 days and the lowest at M0 is 44 days. The highest number of colonies (CFU) in M6 treatment was 1.96 x 10 -12 CFU / g and the lowest was maintenance of M3 1.03 x 10-12 CFU / g.